Konstruksi Kerentanan dan Perlindungan Anak Korban Nikah Siri dalam Perspektif DP3AP2 DI YOGYAKARTA - Mansur; Adika Arif Raya Hidayat Fitroh; Muhammad Fadel Adhyputra (Universitas Islam Negeri Mataram, 2026)
Unregistered marriage (nikah siri) continues to create legal and social challenges for children, particularly regarding legal identity, access to public services, and the protection of their rights. Despite existing legal protection mechanisms, children born from unregistered marriages remain vulnerable to administrative barriers, social stigma, and violence. This study aims to analyze how the Regional Office for Women's Empowerment, Child Protection, and Population Control of the Special Region of Yogyakarta (DP3AP2 DIY) constructs the vulnerability and protection of children affected by nikah siri and to examine the institution’s role in responding to such vulnerabilities. This research employs an empirical legal approach with a qualitative method. Primary data were obtained through semi-structured interviews with key informants from DP3AP2 DIY, while secondary data were collected from legislation, institutional documents, performance reports, and relevant literature. Data were analyzed using Robert N. Entman’s framing model and interpreted through Martha Albertson Fineman’s Vulnerability Theory. The findings show that DP3AP2 DIY frames nikah siri as a structural problem that disrupts legal recognition of marriage, exposing children to risks related to legal identity, education, social protection, bullying, and violence. Such vulnerability is attributed to cultural acceptance of unregistered marriage, parents’ pragmatic motives, and institutional barriers in implementing legal protection. In response, DP3AP2 promotes marriage legalization through isbat nikah, integrated birth certificate services, and cross-sectoral collaboration as key protection strategies. However, this study identifies a gap between existing protection mechanisms, such as the Statement of Absolute Responsibility (Surat Pernyataan Tanggung Jawab Mutlak-SPTJM), and the institution’s protection framework, which remains largely oriented toward marriage legalization. Consequently, stronger institutional capacity and broader access to existing protection mechanisms are needed to ensure more responsive child protection.